2(x-1)+8=7(x+12)

Simple and best practice solution for 2(x-1)+8=7(x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-1)+8=7(x+12) equation:


Simplifying
2(x + -1) + 8 = 7(x + 12)

Reorder the terms:
2(-1 + x) + 8 = 7(x + 12)
(-1 * 2 + x * 2) + 8 = 7(x + 12)
(-2 + 2x) + 8 = 7(x + 12)

Reorder the terms:
-2 + 8 + 2x = 7(x + 12)

Combine like terms: -2 + 8 = 6
6 + 2x = 7(x + 12)

Reorder the terms:
6 + 2x = 7(12 + x)
6 + 2x = (12 * 7 + x * 7)
6 + 2x = (84 + 7x)

Solving
6 + 2x = 84 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
6 + 2x + -7x = 84 + 7x + -7x

Combine like terms: 2x + -7x = -5x
6 + -5x = 84 + 7x + -7x

Combine like terms: 7x + -7x = 0
6 + -5x = 84 + 0
6 + -5x = 84

Add '-6' to each side of the equation.
6 + -6 + -5x = 84 + -6

Combine like terms: 6 + -6 = 0
0 + -5x = 84 + -6
-5x = 84 + -6

Combine like terms: 84 + -6 = 78
-5x = 78

Divide each side by '-5'.
x = -15.6

Simplifying
x = -15.6

See similar equations:

| 4x+18=7(x+39) | | 7-10x=37-31x | | 5y-[2(y+1)+2]=7y | | 9+b=14 | | 17x(-29)-46= | | 44-7x=11x+18 | | 163-4x=6x+23 | | 14-8x=114-43x | | 2y-28=-38 | | -138-9x=7x+22 | | 3x+15+2x+2+x-3=50 | | 2x+10=55-3x | | x-(4-x)=5(x+1)+x | | 6x+10=-107-7x | | j=47+25 | | y^2-6y+9=6 | | 8x-6x+36=7x-2x | | 6(z+1)= | | 150+p+325= | | 67-3x=7-7x | | 0.23y-0.6=0.13y+0.7y | | 5x+219=14x-6 | | 4x-3=14x-73 | | 2r-6=-55+9r | | -3x^2-x+2=0 | | 3x+7x+2x=6 | | -5x+2=3x-6 | | 282-6x=39x+17 | | x-.07=8.22 | | x^2+2x+1=7 | | -20t=160 | | 4(y-7)=2y-28 |

Equations solver categories